Power + Fashion - Geczy A; Karaminas V (Copenhagen Business School, 2024)
“Power dressing,” itself a women’s dress reform movement, as it came to be called in the 1970s, used to distinguish typical feminine dress styles and was seen as a necessary strategy for a more subdued image on par with the masculine, serious, and formal professional dress, namely the ubiquitous suit and tie. This new ‘career’ woman became visible by her appearance and choice of dress codes that reinforced her position as a businesswoman who was seriously committed to her work. But from the perspective of the first decades of the new millennium, power dressing and power and fashion have far wider meanings and ramifications. For Michel Foucault, power is a regulatory principle that is used to control social interactions and to impose structures that inform the ways in which we act and appear. In line with Foucault’s analysis, to dress is already to respond to tacit frameworks of power, and because it involves already accepted codes of visualisation and behaviour, to “power dress” is not simply to wield or enact power voluntarily but to succumb to it as well. Further, as this paper will reveal, power dressing can also be understood according to Foucault’s “technologies of self”, which sees the historical subject as both subject and object of a network of discursive forces that are considered normative as opposed to constructed. Power dressing still exists today but according to a more nuanced and multivalent configuration. It can also be thought of as a particular form of renunciation that facilitates an embodiment of power much as religious asceticism and privation is (purportedly) constitutive of a more authentic self.
Keywords: power; fashion; dress; subject-position; fashion semiology